Analyse de la dimension interculturelle du manuel « Version Originale 1 » - OTROSHI Mohamad-Hossei; ABDOLTAJEDINI Kamyar (Recherches en didactique des langues et des cultures)
In order to promote the acquisition of intercultural communication skills, foreign language Textbooks have tried to focus on communication scenes based on intercultural interactions. Within this framework, the current study is an attempt to analyze the functions of the intercultural interactions presented in the textbook "Version Originale 1". This book targets adult and teenage learners of French as Foreign Language (FFL) at the beginner level (A1). For this level, the theoretical framework of the textbook is action-oriented approach. The inclusion of cultural realities of both the target language and learner’s first language may help learners understand the relativity of their cultural identity and therefore to question their view of otherness. The analysis shows that the manual has not been successful in introducing the necessary cultural and intercultural steps within a communicative approach or action-oriented approach.